Interreligious Dialogue as a Communicative Process: Intersubjectivity and Misunderstandings in Brescia - Maddalena Colombo (Religions, 2025)
This article stems from the PRIN GOV_REL (Urban Governance of Interreligious Dialogue) research project carried out in four Italian cities in 2023–2025 and reports on some preliminary results of the empirical enquiry held in the city of Brescia. The Brescia area is characterised by high rates of residents with an immigrant background and a consolidated presence of religious minorities (Muslim, Orthodox, Sikh, Hindu and Protestant groups), many recognised centres (mosques, temples and Christian non-Catholic churches) and a significant commitment of ethnic–religious communities to local public life. This paper examines the creation of grassroots-level interreligious dialogue, seen as a communicative process. The empirical evidence is based on material collected by participant observations and semi-structured interviews regarding four initiatives that occurred in 2024. A sociocultural analysis outlines the communicative frame: text; context; aims; acts; interlocutors and their power/freedom of expression; interactions; results. The article examines the communicative pattern of each initiative, considering an intercultural orientation and a pluralistic model of interfaith dialogue. It seeks to answer the following questions: what was the fundamental message that the promoters wanted to convey? How do the single actors communicate their perspective of religious “others”, and what results did they achieve or not achieve? The analysis leads to identifying the patterns that facilitate and/or hamper dialogue, taking into account misunderstandings and “cul-de-sac” aspects. Final recommendations highlight the recurrent breaking points that should be prevented and some premises to guarantee successful communication between members of different religions in multicultural urban spaces.